Appendiculo-ileal knot presenting at the third trimester of pregnancy. Issue 6 (14th June 2019) - Abebe, Engida; Tsehay, Ayelign; Lemu, Befekadu; Abebe, Kirubel; Redi, Sultan
Abstract: Though appendicitis is the most common cause of acute abdomen, the vermiform appendix as a cause of small bowel obstruction is a rarity. The inflamed appendix can cause obstruction by making a knot around the small bowel. There are only few case reports on Appendico-ileal knotting (AIK). We have not found any report on AIK causing small bowel obstruction during pregnancy. The diagnosis of acute abdomen in pregnancy is difficult due to the accompanying anatomic and physiologic changes. Because obstruction due to AIK present like any other cause of obstruction diagnosing the condition pre-operatively is uncommon. Here, we report 30 years old Gravida 9, Para 8 women who presented with cardinal symptoms of small bowel obstruction at term and found to have AIK intra-operatively. The challenge of difficulty in making the diagnosis and management options are discussed